Revitalisasi Pendidikan Guru Untuk Menjawab Tantangan Abad 21 - Desti Mutiara Br Ketaren; Rosita Nazila; Cut Kumala Sari (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
The 21st century is marked by rapid technological developments, increasingly open global access, and increasing complexity in social life. This requires significant changes in the education system, especially in terms of the role and competence of teachers. Therefore, teachers are required to be able to adapt to the times, including in terms of the use of technology that continues to develop. In this era, teachers need to master technology well, for example by creating ICT-based learning media, utilizing learning applications, and various other forms of innovation. This study uses a qualitative research method with a descriptive approach. This article emphasizes that to face the challenges of education in the 21st century, teachers are not enough to only act as conveyors of material. Teachers must also be able to be facilitators, guides, and innovators in the teaching and learning process. With this broader role, teachers are expected to be able to improve the quality of basic education and respond to the needs of the times effectively.